Host Based Intrusion Detection Using Data Mining Methodologies - Lakshmi, M. Naga Surya; Sunitha, K V N (International Journal of Computer Sciences and Engineering, 2025)
In today’s computing world there is an inconceivable growth in the usage of computers over different networks and domains, which in turn increases the security threats in terms of intrusions. An intrusion can be either internal or external and the conventional methods used in the detection of intrusion are failed to meet the necessities of preventing and detecting threats or intrusions. In this paper, Data Mining methodologies are combined to handle some of the problems like data Preparation, pre-processing of the data, data classification and Intrusion Detection. The definitive role of IDS is to recognize threats or attacks in contrast to computing schemes. The intrusion detection system is one of the vital networks shielding device or software for safeguarding computing schemes and it is capable to discover and to examine network traffic data packets. This research paper is developed situated on advanced snort rules have been developed. The main goal of this research paper is to detect fraudulent network traffic